Geographic Distribution of Human Infections with Zoonotic Ancylostoma ceylanicum and Anthropophilic Hookworms in Ecuador: A Retrospective Analysis of Archived Stool Samples. - Aguilar Rodríguez, Dayana (2024)
tablas, mapas